2016
DOI: 10.1037/cdp0000078
|View full text |Cite
|
Sign up to set email alerts
|

The culture of mentoring: Ethnocultural empathy and ethnic identity in mentoring for minority girls.

Abstract: The results of this preliminary study suggest that mentors' cultural identity and empathy may be linked with mentees' willingness to explore their own ethnic identities. We discuss the implications for mentoring programs that seek to build participants' ethnic identities and ethnocultural empathy. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Limitations notwithstanding, the findings support past research focused on the importance of mentor and youth characteristics in mentoring relationship quality (e.g., Karcher et al, 2005;Zinn, 2017) and the role of mentors' cultural skills in their relationships with girls of color (Leyton-Armakan et al, 2012;Peifer et al, 2016). Whereas the mentoring literature has focused more attention on the differences in youth outcomes between cross-versus same-race mentoring relationships (e.g., Rhodes, Reddy, Grossman, & Lee, 2002), this study responds to calls to examine racialϪethnicϪcultural processes that influence mentoring relationships and outcomes (Albright, Hurd, & Hussain, 2017;Sánchez et al, 2014).…”
Section: Limitationssupporting
confidence: 79%
See 1 more Smart Citation
“…Limitations notwithstanding, the findings support past research focused on the importance of mentor and youth characteristics in mentoring relationship quality (e.g., Karcher et al, 2005;Zinn, 2017) and the role of mentors' cultural skills in their relationships with girls of color (Leyton-Armakan et al, 2012;Peifer et al, 2016). Whereas the mentoring literature has focused more attention on the differences in youth outcomes between cross-versus same-race mentoring relationships (e.g., Rhodes, Reddy, Grossman, & Lee, 2002), this study responds to calls to examine racialϪethnicϪcultural processes that influence mentoring relationships and outcomes (Albright, Hurd, & Hussain, 2017;Sánchez et al, 2014).…”
Section: Limitationssupporting
confidence: 79%
“…Although Peifer et al (2016) did not find that mentor race influenced the association between ethnocultural empathy and ethnic identity exploration, theory suggests that mentor race (White vs. person of color) may actually moderate the association between other mentor cultural skills and mentee ethnic identity. Because of the marginalization of people of color in the United States, they typically engage in meaning-making about their racial and ethnic experiences compared to that of other individuals and groups (Rivas-Drake et al, 2014).…”
Section: Culturally Relevant Mentor and Youth Characteristics And Out...mentioning
confidence: 65%
“…Additionally, empirical research on mentor's cultural humility suggests that it can play a positive role in the relationship. For example, a mentor's ability to empathize with the experiences of different racial/ethnic groups was found to be positively associated with ethnic identity exploration among adolescent girls of color, regardless of the mentor's racial/ethnic identity (Peifer et al, 2016). Other evidence supports this finding, wherein mentor support for racial/ethnic identity was linked to greater ethnic identity exploration, but only for girls of color paired with a White mentor (Sánchez et al, 2019).…”
Section: Mentor Training Is One Piece Of the Theory Of Change In Rela...mentioning
confidence: 86%
“…From response b) The notion of culture in mentoring was investigated by Peifer et al (2016), who found out that in cross-cultural mentorship, mentors who are empathetic succeed in bringing out the mentees so they can overcome cultural differences and get the mentorship done. Louis (2015) concurred, stating that cross-cultural mentoring could benefit the mentoring profession.…”
Section: Category 6: Lack Of Mergingmentioning
confidence: 99%